Pengaruh Motivasi dan Komitmen Terhadap Produktivitas Karyawan Departemen Produkssi PT. Semen Tonasa (Persero) Tbk Unit Tonasa di Kabupaten Pangkep - Akbar, Muh Irsyad Abror Putra Raja; Tawe, Amiruddin; Burhanuddin, Burhanuddin; Sahabuddin, Romansyah; Nasir, Uhud Dharmawan (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to investigate how work motivation and work commitment affect employee productivity at PT. Semen Tonasa. This study uses a quantitative approach, The analysis method in this study uses the Research Instrument test, Classical Assumption Test, and Multiple Linear Regression Analysis. The results of this study indicate that commitment and motivation have a significant effect (21.7%) on the productivity of company employees. Motivation does not have a significant effect (9%) on employee productivity, Commitment has a significant effect (42.8%) on employee productivity.